Women of the Afghan War - Ellis, Deborah, 1960- (Praeger, 2000)
Annotation This book is an account of the Afghan War and its tragic aftermath as told by the women who were caught up in it and became its innocent victims. The voices in this oral history will provide personal snapshots to the news reports of the Taliban activities now coming out of Afghanistan. These accounts provide an historical background to the growth of the Taliban, and reveal circumstances of the daily life of the women who must survive in this very closed society.
Keywords: Taliban.; Talibans.; Taliban; Women -- Afghanistan -- Social conditions.; Afghanistan -- History -- Soviet occupation, 1979-1989 -- Personal narratives.; Afghanistan -- History -- 1989-2001.; Oral history.; Islam and politics -- Afghanistan.; Islamisme -- Afghānistān.; Femmes -- Afghānistān -- Conditions sociales.; Histoire orale.; Afghānistān -- Histoire -- 1979-1989 (Intervention soviétique) -- Récits personnels.; Afghānistān -- Histoire -- 1989-; Afghānistān -- Histoire -- 1989-2001.; oral histories (literary genre); SOCIAL SCIENCE -- Feminism & Feminist Theory.; Oral history; Women -- Social conditions; Afghanistan; Afghanistan-Konflikt -- 1979-1989; Erlebnisbericht; Soziale Situation; Frau; Geschichte 1980-2000.; Geschichte 1994-2000.; 1979-2001; Personal Narrative; History; Personal narratives; Personal narratives.; Récits personnels.